Aesthetic treatment in grade three dental fluorosis of Thylstrup-Fejerskov index, using conservative methods - Chico Lara, Jerely Normanda (2020)
The lack of harmony in a patient's smile affects their self-esteem and behavior with their environment. Ecuador has been considered an endemic zone of fluorosis, triggering aesthetic and functional dental alterations. Fluorosis appears as opaque spots that follow a horizontal pattern in its early phase and brown spots and loss of structure in an advanced stage. In this article we present the case of a young patient, diagnosed with dental fluorosis grade three of Thylstup-Fejerskov (TF) index, treated with 40% hydrogen peroxide bleaching, followed by 35% peroxide carbamide home whitening for 30 minutes daily, during 7 days. The combination of whitening procedures was ideal to mimic the mottling characteristic of dental fluorosis, thus improving the aesthetics of the patient and guaranteeing the success of the present case. The use of a conservative treatment was effective to restore dental aesthetics, function and confidence of the patient when smiling.